Arterial vascularization of the renal divisions of the domestic fowl - Ş. Hakan Atalgın; E. Ümran Bozkurt; İbrahim Kürtül; Nejdet Dursun (Eurasian Journal of Veterinary Sciences)
The aim of this study was to reveal the vascularization of the divisions of the kidneys. In the study, 20 Ross 308 broiler fowls(Gallus domesticus) averaging 1980+20 gr and obtained from a local breeding station in Ankara were used. Arterial system of the 10 animals was filled with colored latex. The descending aorta of the others were ligated from the level whereafter the ischiadic artery arose, and were filled the latex. Supply area of the cranial, middle, and caudal renal arteries were observed. Additionally, the left cranial division of the kidney was received blood from a branch of the cranial oviductal artery. The middle division was nourished by the branches from the cranial and middle renal arteries while the caudal division was vascularized by the caudal renal artery.